PENGARUH PENAMBAHAN UMBI WORTEL DAN RIMPANG JAHE MERAH TERHADAP DAYA TERIMA DAN DAYA SIMPAN ROTI BOLU DENGAN PENAMBAHAN AMPAS TAHU - Nurpitasari, Dewi; Suparti, Suparti; Asngad, Aminah; Djumadi, Djumadi (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
This study aimed to determine the effect of carrot tuber and red ginger rhizome addition on the acceptability and shelf life of sponge cake enriched with tofu dregs. The research used an experimental method with a Completely Randomized Design (CRD) in a factorial pattern consisting of two factors. The first factor was carrot addition (20%, 30%, and 40%), and the second factor was red ginger addition (9%, 10%, and 12%). Organoleptic evaluation included color, aroma, taste, texture, and crumb structure assessed by panelists. Shelf life observation was conducted at room temperature. The results showed that the best treatment based on overall acceptability was 20% carrot and 12% red ginger (W1J3). This treatment produced a bright color, distinctive aroma, balanced taste, soft texture, and fine crumb structure. Shelf life analysis indicated that the W1J3 treatment had the longest storage period, lasting up to 6 days at room temperature. The addition of carrot and red ginger significantly influenced both acceptability and shelf life. It can be concluded that the incorporation of 20% carrot and 12% red ginger improves the sensory quality and extends the shelf life of tofu dregs sponge cake.